2021
DOI: 10.1590/1678-7757-2020-0266
|View full text |Cite
|
Sign up to set email alerts
|

Dentinal tubule occlusion using Er:YAG Laser: an in vitro study

Abstract: Objectives: We analyzed the effects of the Er:YAG laser used with different parameters on dentinal tubule (DT) occlusion, intrapulpal temperature and pulp tissue morphology in order to determine the optimal parameters for treating dentin hypersensitivity. Methodology: Dentin specimens prepared from 36 extracted human third molars were randomized into six groups according to the treatment method (n=6 each): control (A); Gluma desensitizer (B); and Er:YAG laser treatment at 0.5 W , 167 J/cm2 (50 mJ, 10 Hz) (C), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…In the treatment of dentin hypersensitivity, various lasers are currently employed, including Nd:YAG, Er:YAG, Er Cr:YSGG, and diode lasers [ 35 ]. The effectiveness of Nd:YAG lasers in providing efficient tubule occlusion and penetration depth for the treatment of DH was reported [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the treatment of dentin hypersensitivity, various lasers are currently employed, including Nd:YAG, Er:YAG, Er Cr:YSGG, and diode lasers [ 35 ]. The effectiveness of Nd:YAG lasers in providing efficient tubule occlusion and penetration depth for the treatment of DH was reported [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the effectiveness of the Er:YAG laser in occluding dentin tubules is due to the absorption of laser irradiation by water molecules within hydroxyapatite, leading to dentin ablation and subsequently causing the melting and recrystallization of the dentin [ 39 , 40 ]. Zhuang et al [ 35 ] investigated the effect of Er:YAG laser application on dentin tubule occlusion and intrapulpal temperature increase and its impact on pulp using different parameters (0.5 W/50 mJ/10 Hz, 1 W/50 mJ/20 Hz, 2 W/100 mJ/20 Hz, and 4 W/200 mJ/20 Hz). As a result, they found the 0.5 W and 50 mJ setting to be effective for dentin tubule occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were initially immersed in a solution of 2.5% glutaraldehyde (Cidex, Johnson & Johnson India, Mumbai, India) for a duration of 12 hours at a temperature of 4 °C. This immersion served to effectively conserve the samples and stabilize the dentinal tubules prior to their examination through SEM [ 12 ]. Following this preservation step, a chemical dehydration procedure was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the assessment of the intrapulpal temperature stabilization and pulp tissue morphological invariability was also conducted. In addition, the extracted human molars after Er:YAG laser irradiation at 0.5 W (167 J/cm 2 ) showed superior dentin tubule occlusion, less intrapulpal temperature change, and hardly any morphological alterations of the pulps [ 104 ]. The dentine of different thicknesses was irradiated with a Nd:YAP laser in an ex vivo study; whilst conducting this, they found that a Nd:YAP laser at a PD of 356 W/cm 2 had a significant effect on the diameter change in dentinal tubule orifices and caused less of an increase in temperature [ 25 ].…”
Section: Lasers In Dentinal Hypersensitivity Treatmentmentioning
confidence: 99%